RELATIONSHIP BETWEEN THE Q223R LEPTIN RECEPTOR GENE SINGLE NUCLEOTIDE POLYMORPHISM AND THE LIPID PROFILE IN PATIENTS WITH DISCIRCULATORY ENCEPHALOPATHY - Паленка, О.Є.; Литвиненко, Н.В. (World of Medicine and Biology, 2015)
Excessive weight and obesity are among the main potentially modified risk factors for vascular diseases. Epidemiological surveys have conclusively proven the relationship between overweight, obesity and cardiovascular diseases. A comprehensive clinical and diagnostic research and analysis of the Q223R leptin receptor gene polymorphism have been carried out in the whole cohort of discirculatory encephalopathy patients (80 persons). Analyses of demographic parametres, anthropometric investigation data and biochemical and genetic tests were applied in the research. The discirculatory encephalopathy patients showed three different genotype variants: homozygous QQ (the “wild”, natural variant – 14 persons, 17.5 %), heterozygous QR (50 persons, 62.5 %) and homozygous with the RR polymorphism (16 persons, 20 %). The patients with the QQ genotype made the first group, those with the QR genotype made the second group and those with the RR genotype made the third group. The population structure of the patients under investigation was dominated by the QR heterozygotes. Female patients prevailed in all groups, particularly in the group with the RR genotype. It was revealed significantly longer duration of vascular encephalopathy in the group with genotype RR, which was indicative of the beginning of the disease at a younger age. Body weight and BMI were apparently higher in the group with the homozygous QQ genotype compared to the heterozygous QR group. The homozygous RR genotype was associated with higher triglyceride concentration compared to the QQ and QR genotype groups; however, there was no apparent difference in triglyceride concentration observed between the QQ and QR genotype groups. The other lipidogram parameters (total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, atherogenetic index) did not differ in the different LEPR genotype groups. The investigation results will constitute a ground for a base which will be used to search for markers of liability to diseases the predictor of which is excessive weight.
Keywords: discirculatory encephalopathy; Q223R leptin receptor gene polymorphism; lipid profile